Transparent AMOLED display driven by split oxide TFT backplane. Issue 3 (16th April 2018) - Lee, Suhui; Chen, Yuanfeng; Kim, Jeonggi; Kim, Hyo‐Min; Jang, Jin
Abstract: We have developed stable and high performance etch‐stopper amorphous indium–gallium–zinc oxide thin‐film transistor (TFT) by using split active oxide semiconductor. The amorphous indium–gallium–zinc oxide TFTs exhibit the mobility as high as over 70 cm 2 /Vs and the stable operation under positive bias temperature stress. In this work, we demonstrated a 4‐in. transparent active‐matrix organic light‐emitting diode display using oxide TFT backplane with split active layer, where the gate driver is integrated. Abstract : Extremely stable high performance etch‐stopper (E/S) amorphous indium–gallium–zinc oxide thin‐film transistor (TFT) by using split active oxide semiconductor. The transistors showing the high mobility over 70 cm 2 /Vs and extremely stable behavior under positive bias temperature stress. In this work, we demonstrated a 4‐in. transparent active‐matrix organic light‐emitting diode display using oxide TFT backplane with split active layer, where the gate driver is integrated.